2018
DOI: 10.1590/1980-5373-mr-2017-0715
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Friction and Wear Properties of High-Temperature Bearing Steel 9Cr18Mo

Abstract: This paper presented a study of friction and wear on 9Cr18Mo when rubbed against other materials (steel-304, steel-440C, steel-GCr15 or silicon nitride ceramic ball) at high temperature conditions. Friction and wear tests were carried out with universal a friction and wear testing machine. The wear morphology was analyzed by a Nanovea three-dimensional profilometer and trinocular positive Gang metallurgical microscope. The Vickers hardness of 9Cr18Mo at different temperatures was tested by means of a high temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Hu X F et al [4] conducted a study on the influence of discrete surface laser quenching on the friction and wear performance of 25CrNi2MoV steel and found that the use of a discrete surface laser quenching process led to a substantial decrease in the wear volume of the samples by approximately 93.2%. As for the study of the wear resistance of steel at different temperatures, this also has a lot of research such as He Q [5] et al and Emami M [6] et al studied the wear resistance of 9Cr18Mo steel and 31CrMoV9 nitride steel at various high temperatures, respectively. However, there is limited research on the investigation of friction and wear characteristics of steel at varying temperatures after USR treatment.…”
Section: Introduction Aisi 8620hmentioning
confidence: 99%
“…Hu X F et al [4] conducted a study on the influence of discrete surface laser quenching on the friction and wear performance of 25CrNi2MoV steel and found that the use of a discrete surface laser quenching process led to a substantial decrease in the wear volume of the samples by approximately 93.2%. As for the study of the wear resistance of steel at different temperatures, this also has a lot of research such as He Q [5] et al and Emami M [6] et al studied the wear resistance of 9Cr18Mo steel and 31CrMoV9 nitride steel at various high temperatures, respectively. However, there is limited research on the investigation of friction and wear characteristics of steel at varying temperatures after USR treatment.…”
Section: Introduction Aisi 8620hmentioning
confidence: 99%
“…Comparing with two-dimensional (2D) images, the 3D measurements can show more wear surface morphology characteristics and surface parameters, such as the arithmetic mean deviation, root mean square deviation, maximum peak valley depth, and maximum peak valley height. 12 He et al 13 carried out the performance test of the 9Cr18Mo-steel hybrid pair and analyzed the wear surface morphology, friction coefficient and Vickers hardness of the 9Cr18Mo by Nanovea three-dimensional profiler and metallographic microscope. Yang et al 14 studied the sliding friction and wear behavior of the plasma-sprayed aluminum-bronze coating and Si 3 N 4 , and analyzed the morphological characteristics of the worn surface by 3D non-contact surface mapping and scanning electron microscope.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The tribological characteristics of spherical plain bearings have played a very significant role in the design and processing of pertinent parts and motion systems 4 since the friction in bearings will inevitably impede the normal dynamics of mechanical systems, disturbing the force transfer process and impairing the transmission efficiency. 5 Over the past decades there have been increasing research efforts to measure and improve the systems’ tribological performance, involving a series of experimental methods to test the friction coefficient of bearings, 6,7 modify the surface texture, 8 evaluate the failure load 9,10 and so on.…”
Section: Introductionmentioning
confidence: 99%